Content analysis of cell division concepts in Senior High School Biology textbooks - Eva Niña B. Lopez; Chris Mae B. Maraño; Ritchelle W. Origenes; Aylene D. Pizaña; Josephine M. Salmo; Jay P. Picardal (University of Muhammadiyah Malang, 2022)
Content and accuracy evaluation of textbooks is important as it provides quality assurance to both teachers and learners, especially in the new normal where modular instruction is used. This research aimed at evaluating the biology textbooks used by Senior High School STEM Science teachers (n=15) in content, presentation, and learning strategies. Content analysis and Collaizzi’s descriptive phenomenology approach were employed in this study. The results showed that all evaluated textbooks have unique, distinct content, presentation, and learning strategies. Most topics were also aligned with the minimum curriculum requirement for SHS STEM, but topics such as cyclin-dependent kinases (CDKs) and control checkpoints were not discussed in some books. Learning outcomes were not indicated in some books, and few textbooks did not reach synthesis and evaluation level. However, a comparative approach of cell division across the 5-kingdom system is observed but not explained well, and some misleading statements in the cell division mechanism were present. Considering that cell division precedes the discussion of cancer cell division and metastasis, content enrichment through learner-friendly visuals and diagrams is recommended to facilitate learning, improve retention, and avoid misconceptions.